Pengembangan dan Validasi Teoretis Model PJBL–STEAM–IC untuk Meningkatkan Keterampilan Berpikir dan Kesadaran Lingkungan Siswa di Sekolah Pesisir - Srilesnawati Lalusu; Elya Nusantari; Frida Maryati Yusuf; Abubakar Sidik Katili; Hartono Mamu; Muhammad Rifai Katili; Masra Latjompoh (Postgraduate, University of Mataram, 2026)
Coastal science learning in Pagimana, Central Sulawesi, has not adequately connected local environmental problems with students’ thinking development and environmental awareness. This study aimed to develop and examine the expert validity of the PjBL-STEAM-IC model, in which IC denotes Innovation and Creativity, for SOLO-based thinking skills and environmental awareness in coastal schools. Using an adapted Borg and Gall research and development procedure, this article reports the needs analysis, hypothetical model design, development of instructional materials and research instruments, expert validation, and Product Revision I. Three validators evaluated the model and its supporting products; their ratings were analysed using Aiken’s V, and their written recommendations were examined descriptively. The developed model comprises six phases linking coastal environmental problems, STEAM-IC project activities, SOLO-based reasoning, and four dimensions of environmental awareness: knowledge, attitude, behaviour, and skills. All validated components were classified as very valid, with Aiken’s V coefficients ranging from 0.902 to 0.961. Expert feedback led to clearer operational syntax, stronger theoretical mapping, more explicit STEAM-IC integration, improved alignment with SOLO-based thinking and environmental awareness, and refinement of the student response questionnaire. The model and its supporting products were therefore considered sufficiently valid to proceed to subsequent classroom field testing.